THE NOTION OF MACROPHRASING IN TEXT LINGUISTICS - Israilov, G’ayrat (FILOLOGIYA UFQLARI JURNALI, 2023)
Structural linguistics as one of the most interesting areas of text linguistics in the field of the literary works analysis is a set of views on the language and methods of its study. It is based on the understanding of language as a sign system with clearly distinguished structural elements and a tendency to exact formal language description [12, 496]. The depth and surface text structures detection is possible within these scopes. However, it should be taken into consideration that there have been certain differences in the structure of poetry and any other literary text.